Extraction and characterization of biofunctional lignocellulosic fibers from Pulicaria undulata plant and the effect of alkali treatment on their bio-physicochemical properties - Mohammed, Alsafran (2024)
This study aimed to extract and characterize natural fibers from the P. undulata plant and to evaluate their antioxidant and antimicrobial activities, including the influence of alkali treatment on the bio-physicochemical properties. The average yield of raw fibers obtained was 28.1 %. The raw fibers of P. undulata were rich in cellulose (36.2 %), followed by hemicellulose (30.3 %), lignin (16.2 %), moisture (11.1 %), and pectin (3.9 %). However, the alkali treatment removed 75.7 % of hemicellulose and 50.6 % of lignin from the raw fiber sample and also increased its crystallinity and hydrophobicity. Similarly, the degradation temperature of P. undulata fibers also increased from 324.4 °C to 332.6 °C after alkali treatment. The raw fiber showed promising radical scavenging and reducing power properties, and demonstrated antifungal activity against Candida albicans. In contrast, alkali-treated fibers showed a significant decrease in radical scavenging activity (almost 7–8 fold) and reducing power potential (6-fold) and exhibited no antifungal activity, potentially due to the loss of bioactive components such as lignin and essential oils. Overall, the findings of this study highlight the potential applications of raw P. undulata fibers in the healthcare and cosmetics products.